Numerical study of heat transfer during solidification in ice-freezing type PCM heat exchanger. (2021) - Patel, Parth; Sharma, Manvendra; Mondal, Bobin; Kothadia, Hardik
Abstract: In these modern times, the requirement of the energy is not always constant but often periodic. In a hot climatic country like India, a large amount of energy is consumed in cooling application. A heat-exchanger which can store the thermal energy during off-peak hours and use the same energy during peak hours for cooling applications may flatten the periodic energy requirements. Water has a very high value of latent heat of fusion. This latent heat can be utilized to store the thermal energy and use it at a later stage for cooling purposes. The cooling temperature management will be more effective during the phase change process due to the constant fluid temperature. The present study analyzes the heat transfer performance of Ice-Freezing type phase change material (PCM) based heat-exchanger (HEX) during the solidification process. The prediction of solidification time and variation of heat transfer coefficient (HTC) under various configurations is performed. commercialized computational fluid dynamics (CFD) software, Fluent 19 is used to analyze the solidification phenomenon in water. To evaluate the optimum element size, Mesh-independent study is conducted on a single block. Initially, the single block is considered for analyzing the solidification process. The simulations are performed on multiple pipe with varying pitch. The results indicated a drastic change in solidification time as the pitch is decreased. An optimum pitch has to be decided based on the application. The transient variation of the HTC during the solidification process is studied. Initially, during the sensible cooling stage, the HTC decreases at a faster rate. While during the solidification process, the transient variation in HTC is less.